The Active Fractions from Ethanol Extracts of Gracilaria Coronopifolia J Agardh Are Potential Free Radical Scavenging Agents - I Made Dira Swantara; Sagung Chandra Yowani ; Osamu Iitsuka (Journal of Applied Chemical Science, 2012)
Six compounds in one fraction of seaweed Gracilaria coronopifolia (Red algae) that have radicalscavenging activity have been identified. Extraction of those compounds was carried out by maceration method using 96% ethanol. Separation and purification of the fraction were performed by liquid-liquid partition and column chromatographic methods. The obtained fractions were treated with 2,2-diphenyl-1- picrylhydrazyl and found that their radical-scavenging activities of the first (A) and the second (B) fractions from the column with a 60 min retention time were 83.12% and 90.72%, respectively. The compounds contained in the A and B fractions identified by GC-MS were 1-nonadecene; hexadecanoic acid or palmitic acid; octadec-9-enoic acid; cholesta-4,6-dien-3β-ol; cholest-5-en-3β-ol or cholesterol; and cholest-4-en-3- one. These compounds could be expected to have radical scavenging activities.